2002
DOI: 10.1164/rccm.2110016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Severe Isolated Unilateral and Bilateral Diaphragm Weakness on Exercise Performance

Abstract: Patients with isolated diaphragm paralysis depend on recruitment of extradiaphragmatic respiratory muscles to increase ventilation, but little is known about exercise performance or the response of the inspiratory muscles to loaded breathing. By convention, unilateral diaphragm paralysis is regarded as a trivial condition whereas bilateral paralysis is considered to be potentially life-threatening. In fact, no data exist concerning exercise performance under these conditions. We studied incremental treadmill e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
0
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 34 publications
6
70
0
8
Order By: Relevance
“…HART et al [7] showed an unexpectedly large reduction in exercise capacity in patients with UDP. LAROCHE et al [32] found UDP patients to be more breathless than expected.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…HART et al [7] showed an unexpectedly large reduction in exercise capacity in patients with UDP. LAROCHE et al [32] found UDP patients to be more breathless than expected.…”
Section: Discussionmentioning
confidence: 95%
“…During sleep in normal subjects, ventilation depends particularly on diaphragm function [3]. In patients with diaphragm dysfunction, during both rapid eye movement (REM) sleep and wakefulness, electromyographic activity of the extradiaphragmatic respiratory muscles [4][5][6][7] is higher than normal as a compensation for diaphragm weakness.…”
mentioning
confidence: 99%
“…The increasing use of accessory respiratory muscles as exercise continues may distort the chest wall (34,36), reduce the mechanical efficiency of breathing (23,42) and, hence, increase the metabolic and blood flow demands of these muscles (see EXERCISE DEMANDS ON THE RESPIRATORY MUSCLES). The progressive recruitment of accessory respiratory muscles would be expected to increase sensory input to the central nervous system and, therefore, increase the intensity of dyspnea.…”
Section: Mechanisms By Which Respiratory Muscle Fatigue Could Affect mentioning
confidence: 99%
“…Patients with unilateral diaphragm paralysis are usually asymptomatic but may have dyspnea on exertion (12). It is known that diaphragm paralysis has an impact on pulmonary function tests by decreasing FVC to 70 -80% of the predicted value, which is further decreased by 15 -25% in the supine position.…”
Section: Impact Of Peritoneal Dialysis On Pulmonary Function Test In mentioning
confidence: 99%